Women music educators in the United States : a history - Howe, Sondra Wieland, 1938- (Women's studies (Lanham, Md.), 2013)
Although women have been teaching and performing music for centuries, their stories are often missing from traditional accounts of the history of music education. In Women Music Educators in the United States: A History, Sondra Wieland Howe provides a comprehensive narrative of women teaching music in the United States from colonial days until the end of the twentieth century. Defining music education broadly to include home, community, and institutional settings, Howe draws on sources from musicology, the history of education, and social history to offer a new perspective on the topic.